Performance Evaluation of Beacon-Enabled Mode for IEEE 802.15.4 Wireless Sensor Network - Al Rasyid, M. Udin Harun; Saputra, Ferry Astika; Fahmi, Alfian (Politeknik Elektronika Negeri Surabaya (PENS), 2013)
IEEE 802.15.5 standard support structure of star and peer-to-peer network formation. Strating from these, the cluster tree network can be built as a special case of peer-to-peer network to increse coverage area. In this paper, we provide an performance evaluation of beacon- enabled mode for IEEE 802.15.4 wireless sensor network on star and cluster topology in order to get the maximum result to apply the appropriate topology model as needed. We conduct analysis on each topology model by using the numbers of nodes from 10 nodes to 100 nodes to analyze throughput, delay, energy consumption, and probability success packet by using NS2 simulator. The simulation results show that the throughput and the probability of success packet of cluster topology are higher than that of star topology, and the energy consumption of cluster topology is lesser than that of star topology. However, cluster topology increases the delay more than star topology.Keywords: IEEE 802.15.4, wireless sensor network, beacon-enabled mode, topology, csma/ca